Fever of unknown origin (FUO) in children: a single-centre experience from Beijing, China. Issue 3 (16th March 2022) - Hu, Bing; Chen, Tian-Ming; Liu, Shu-Ping; Hu, Hui-Li; Guo, Ling-Yun; Chen, He-Ying; Li, Shao-Ying; Liu, Gang
Abstract : Objective: To date, there is no standard diagnostic practice to identify the underlying disease-causing mechanism for paediatric patients suffering from chronic fever without any specific diagnosis, which is one of the leading causes of death in paediatric patients. Therefore, we aimed this retrospective study to analyse medical records of paediatric patients with fever of unknown origin (FUO) to provide a preliminary basis for improving the diagnostic categories and facilitate the treatment outcomes. Design: A retrospective study. Setting: Beijing Children's Hospital. Participants: Clinical data were collected from 1288 children between 1 month and 18 years of age diagnosed with FUO at Beijing Children's Hospital between January 2010 and December 2017. Interventions: According to the aetiological composition, age, duration of fever and laboratory examination results, the diagnostic strategies were analysed and formulated. Primary and secondary outcome measures: The statistical analyses were carried out using SPSS V.24.0 platform along with the χ 2 test and analysis of variance (p<0.05). Results: The duration of fever ranged from 2 weeks to 2 years, with an average of 6 weeks. There were 656 cases (50.9%) of infectious diseases, 63 cases (4.9%) of non-infectious inflammatory diseases (NIIDs), 86 cases (6.7%) of neoplastic diseases, 343 cases (26.6%) caused by miscellaneous diseases and 140 cases (10.9%) were undiagnosed. With increasing age, the proportion of FUO from infectious diseases gradually decreased from 73.53% to 44.21%. NIID was more common in children over 3 years old, and neoplastic diseases mainly occurred from 1 to 6 years of age. Among miscellaneous diseases, the age distribution was mainly in school-aged children over 6 years. Respiratory tract infection was the most common cause of FUO in children, followed by bloodstream infections. Bacterial infection was the most common cause in children with less than 1 year old, while the virus was the main pathogen in children over 1 year old. Conclusions: The diagnosis of neoplastic diseases and miscellaneous diseases-related diseases still depends mainly on invasive examination. According to our clinical experience, the diagnostic process was formulated based on fever duration and the type of disease. This process can provide a guide for the diagnosis and treatment of paediatric FUO in the future.